Could Elko Spinor Fields Induce VSR Symmetry in the DKP (Meson) Algebra? - Cavalcanti, R. T.; da Rocha, R.; Hoff da Silva, J. M. [UNESP] (Springer Nature, 2017)
It is shown that the meson algebra can be faced as the tensor product of Clifford algebras and, then, by constructing the DKP field by means of Elko spinors, we demonstrate that the symmetries of the so called very special relativity are inherited by the DKP field.
Keywords: Clifford algebra; DKP algebra; Elko spinor fields; Meson algebra; VSR symmetry